Determinants of Adolescent Female Behavior for Consumption of Fe Tablets on the Working Area of the Nan Balimo Public Health Center - Agustina, Sarah; Rasyid, Rosfita; Kasra, Kamal (Journal La Medihealtico, 2025)
Anemia remains a significant public health issue among female adolescents, particularly due to iron deficiency. The consumption of iron (Fe) tablets is a primary government-recommended intervention, yet adherence levels remain low. This study aimed to analyze the factors influencing Fe tablet consumption behavior among female adolescents in the working area of Nan Balimo Public Health Center, Solok City. A mixed methods approach with an explanatory sequential design was employed. A total of 293 female adolescents were selected using proportional random sampling and analyzed using chi-square tests and multiple logistic regression. Qualitative data were obtained through in-depth interviews with 11 informants. Multivariate analysis revealed four variables significantly associated with Fe tablet consumption behavior: knowledge, attitude, role of health workers, and media exposure (p ≤ 0.05), with the role of health workers emerging as the dominant factor (p = 0.002; POR = 2.655; 95% CI: 1.429–4.935). The qualitative findings supported these results, highlighting challenges such as irregular tablet distribution, monotonous education, weak monitoring, and suboptimal coordination, all contributing to a stagnation in consumption rates, which declined from 96.6 % to 83.06 % over three consecutive quarters. Enhancing the role of health workers is a strategic key to improving Fe tablet adherence among female adolescents. Therefore, it is essential for health centers and health authorities to strengthen communication skills, counseling, and health worker support capacity, while also ensuring the availability of engaging educational media and intensive monitoring.